Dampak Pandemi terhadap Pemanfaatan e-Learning pada Sekolah Dasar di Den Haag - Atalah Raniah; Jefiska Roman Prantista; Dwi Pangestuti Alfiana; Sangga Firman Aghisni; Eva Luthfi Fakhru Ahsani (Islamic Review: Jurnal Riset dan Kajian Keislaman, 2021)
This study aims to find out how the impact of E-learning in Indonesian schools in the Dutch Hague due to Covid-19. This research uses descriptive qualitative method. Data collection techniques obtained through observation, interviews and documentation study. Data analysis techniques using data reduction, preparation, grouping, and data checking activities. The results showed that the current covid-19 virus also had an impact on E-learning in schools at the Indonesian School The Hague (SIDH), and the effectiveness of online E-learning was also supported by learning using the internet network with accessibility, connectivity, flexibility, and the ability to bring up learning interactions that are usually done through firtual with zoom, Google Classroom and other applications that are tailored to existing policies in SIDH schools.